Bourdieusian Concepts and the Field of Theatre Criticism - Petrikas, Martynas (Nordic Theatre Studies, 2019)
Pierre Bourdieu’s concepts of field sociology began their life in humanities, particularly in literature and art studies after publication of his seminal Les règles de l’art: genèse et structure du champ littéraire in 1992. Regretfully, Bourdieu has not left a study dedicated to theatre, possibly due to the long-standing French tradition of considering theatre as another literary genre. Nevertheless, Bourdieusian sociology is abundant with terms, concepts, and ideas that are extremely handy in analyzing and understanding how theatre was produced in the past and is produced in the present. The appropriation of Bourdieu’s ideas for theatre studies is a tempting effort, especially considering how closely theatre is intertwined with the phenomena of habitus, distinction, and all the forms of capital described by Bourdieu himself. The aim of my article is to discuss the applicability of selected Bourdieusian notions and concepts for research of a very specific aspect of theatre studies. I argue that the concepts of field (champs), nomos, doxa, illusio as well as of symbolic violence are very useful in understanding the nature, functions, and effects of theatre criticism. Dwelling on my own theoretical research, I propose to understand theatre criticism as another field of social practice that is defined by the conflict between the opposing interests of t